The Extent of Applying Quality Assurance and Program Accreditation Standards from Students' Perspective in the Accounting Department, Faculty of Economics and Political Sciences - Tobruk University - Hussam Murajia Alnaas; Rahma Subhi Hussain; Hamdi Attia Hammad; Amna Noah Idris (University of Science and Technology, Yemen, 2021)
The study aimed to investigate to what extent quality assurance and program accreditation standards are applied from students' perspective in the accounting program at the Faculty of Economics and Political Sciences at the University of Tobruk in accordance with the standards of the National Center for Quality Assurance and Accreditation of Educational and Training Institutions. The study used the descriptive and analytical method based on the evaluation form issued by the National Center for the undergraduate programs. The survey forms were distributed to the entire study population of 36 male and female students. Major study findings revealed that quality assurance and program accreditation standards regarding the evaluation aspects of the university study program (educational program, faculty members, educational support services, student affairs, facilities, quality assurance and continuous improvement) are not applied in the accounting program. The study recommended the need to pay attention to quality assurance standards in all items and themes.